Hormonal networks involved in apical hook development in darkness and their response to light - Mazzella, María Agustina (2014)
Fil: Mazzella, María Agustina. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular, “Dr. Héctor Torres” (INGEBI-CONICET). Buenos Aires, Argentina.